Intestinal microbiome changes and stem cell transplantation: Lessons learned. Issue 8 (16th November 2016) - Taur, Ying
ABSTRACT: Studies of the microbiome in the setting of haematopoietic stem cell transplantation (SCT) have shown evidence that intestinal microbes appear to play a particularly important role in determining the outcome of treatment, impacting complications such as infection or graft-versus-host disease. Past studies may vary in terms of the level at which the microbiome is examined, leading to different but overlapping systems of taxonomy or nomenclature, which may be difficult for non-specialists to understand. This article will review the current body of work examining the clinical impact of the microbiome on SCT, and will provide a basic framework for the bacterial phylogenetic structure upon which the results of these studies rest. With this framework it can be shown that recurring patterns do emerge in prior studies identifying the microbes that confer benefit in this population.